In vitro effect of Withania somnifera, AYUSH-64, and remdesivir on the activity of CYP-450 enzymes: Implications for possible herb−drug interactions in the management of COVID-19 - Siva Swapna Kasarla; Siva Swapna Kasarla; Swapnil P. Borse; Yashwant Kumar; Neha Sharma; Neha Sharma; Madhu Dikshit; Madhu Dikshit (Frontiers in Pharmacology, 2022)
Ayurvedic medicines Withania somnifera Dunal (ashwagandha) and AYUSH-64 have been used for the prevention and management of COVID-19 in India. The present study explores the effect of Ashwagandha and AYUSH-64 on important human CYP enzymes (CYP3A4, CYP2C8, and CYP2D6) to assess their interaction with remdesivir, a drug used for COVID-19 management during the second wave. The study also implies possible herb−drug interactions as ashwagandha and AYUSH-64 are being used for managing various pathological conditions. Aqueous extracts of ashwagandha and AYUSH-64 were characterized using LC-MS/MS. A total of 11 and 24 phytoconstituents were identified putatively from ashwagandha and AYUSH-64 extracts, respectively. In addition, in silico studies revealed good ADME properties of most of the phytoconstituents of these herbal drugs and suggested that some of these might possess CYP-450 inhibitory activity. In vitro CYP-450 studies with human liver microsomes showed moderate inhibition of CYP3A4, 2C8, and 2D6 by remdesivir, while ashwagandha had no inhibitory effect alone or in combination with remdesivir. AYUSH-64 also exhibited a similar trend; however, a moderate inhibitory effect on CYP2C8 was noticed. Thus, ashwagandha seems to be safe to co-administer with the substrates of CYP3A4, CYP2C8, and CYP2D6. However, caution is warranted in prescribing AYUSH-64 along with CYP2C8 substrate drugs. Furthermore, preclinical and clinical PK studies would be helpful for their effective and safer use in the management of various ailments along with other drugs.